The Legal Protection of Migrant Workers' Issues in Indonesia Is Examined According to Law No. 39 Of 2004 - Dedi Mulyadi; Fuji Raihan Azhari; Ikhsan Kintara; Shidqi Fauzan Hidayat; Desta Cantika; Rafry Pradipa; Hamada Hadi (PT Syamilah Literasi Islami, 2024)
Indonesian migrant workers are an integral part of the globalization phenomenon that involves the movement of labor across countries. Along with the times and the increasing need for workers in certain sectors, many Indonesians choose to work abroad to improve their economic welfare and that of their families back home. Despite the expectation of improving economic welfare, they often face various challenges requiring adequate legal protection. This research uses a normative juridical research method with a statutory approach by referring to Law No. 39 of 2004 and its related regulations concerning the protection of migrant workers. Through this approach, the research explores the existing legal framework and identifies weaknesses and shortcomings in its implementation. Drawing on previous studies, this research emphasizes the importance of economic welfare and workers' rights, highlighting the need for comprehensive solutions. Through in-depth analysis encompassing workers' backgrounds, legal frameworks, and existing issues, this study aims to contribute to enhancing legal protection for Indonesian migrant workers abroad.